2020
DOI: 10.3390/ijerph17186852
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Health-Related Cardiorespiratory Fitness in Physical Education: The Role of Class Intensity and Habitual Physical Activity

Abstract: Physical education (PE) has the potential to promote health-related fitness, however, its contribution is still not clear. The aim of this study was to assess whether students’ health-related cardiorespiratory fitness (CRF) improved from the beginning to the end of the school year, and to examine the role of PE class intensity and habitual physical activity (PA) in promoting students’ CRF. This observational study employed a longitudinal design. Participants were 212 7th and 8th grade students (105 boys), mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…This experimental result is in line with the findings of Miguel et al. ( 51 ), which showed a positive correlation between participation in organized sports and changes in Pacer (laps). The 8-week RSE participated in by the AWRSE in this study had strict requirements for practice and rest time, which is a more organized form of exercise compared to SG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This experimental result is in line with the findings of Miguel et al. ( 51 ), which showed a positive correlation between participation in organized sports and changes in Pacer (laps). The 8-week RSE participated in by the AWRSE in this study had strict requirements for practice and rest time, which is a more organized form of exercise compared to SG.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there were no significant inter-group differences in Pacer (laps) and VO 2 max after the intervention among the three groups of children, the AWRSE showing a more significant improvement in Pacer, closer to the level of TD children. This experimental result is in line with the findings of Miguel et al (51), which showed a positive correlation between participation in organized sports and changes in Pacer (laps). The 8-week RSE participated in by the AWRSE in this study had strict requirements for practice and rest time, which is a more organized form of exercise compared to SG.…”
Section: Discussionsupporting
confidence: 93%
“…Physical education (PE) class is a key component for promoting health-related behaviors among youth. During the past decades, evidence has accumulated on the positivie association between PE and several outcomes, such as motor skills development 1 , physical fitness 2 , improvement in daily physical activity 3 , health percep-tion and nutrition 4 . In addition, participation in PE class can improve cognitive and academic skills 5 , positive attitude 3,6 and health behaviors 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In endurance sports, the physical fitness changes are evaluated mainly by cardiorespiratory fitness (CRF) testing. The CRF reflects the overall capacity of the cardiovascular and respiratory systems [ 7 ], which is measured, for instance, through maximal or peak oxygen consumption (VO 2 max). CRF could be assessed by various parameters, however, the VO 2 max is considered as a golden standard [ 8 ].…”
Section: Introductionmentioning
confidence: 99%